1996
DOI: 10.1097/00001888-199606000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Medical studentsʼ attitudes toward the autopsy

Abstract: It was concluded that the autopsy elective had a positive influence on the student's attitudes. In addition, the pathologist's behavior and the environment in which the autopsy occurred influenced the students. Twenty-two (85%) of the students indicated the autopsy should be mandatory for all students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…This compares favourably with the study conducted at Ohio (USA) where 85% of the students also said that autopsy should be mandatory for all medical students. 16 But this comes in contrast with the findings of another study which observed that almost one third of the students were ignorant about essentiality of the postmortem examination in the country. 17 It is worth noting that only 3 students opined that post-mortems are conducted to harass the guardians/relatives thus showing a positive attitude towards this procedure.…”
Section: Discussionmentioning
confidence: 71%
“…This compares favourably with the study conducted at Ohio (USA) where 85% of the students also said that autopsy should be mandatory for all medical students. 16 But this comes in contrast with the findings of another study which observed that almost one third of the students were ignorant about essentiality of the postmortem examination in the country. 17 It is worth noting that only 3 students opined that post-mortems are conducted to harass the guardians/relatives thus showing a positive attitude towards this procedure.…”
Section: Discussionmentioning
confidence: 71%
“…7,19,22 The physical environment of the autopsy room, the emotional atmosphere in which the autopsy is carried out, including the way the corpse is handled, and the behaviour of the pathologist have a strong influence on students. 9,23 In this study, one third of the students were satisfied with the way the corpse was handled. Only one quarter thought that the procedure needed no improvement, while the majority suggested that some aspects be modified in order to afford more respect to the deceased.…”
Section: Discussionmentioning
confidence: 77%
“…7 If these feelings and thoughts are not channelled properly, certain students will understandably rapidly develop a coping mechanism to face the frightening autopsy experiences in order to reduce stress and to benefit intellectually from it. 22,23 This mechanism consists of emotional withdrawal and a feeling of detachment from the cadaver having been a human being. 22,24 Students may intellectualise the procedure, dehumanise the corpse through over-professionalism or become habituated to the situation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the latter survey even suggested that the use of the autopsy in medical education may be underutilized and undervalued. A more recent study from the Medical College of Ohio (Conran et al, 1996) reinforced that suggestion, concluding that "the autopsy elective had a positive influence on the students' attitudes." Furthermore, 85% of the students responding to the questionnaire felt that "the autopsy should be mandatory for all students."…”
Section: Compensatory Strategiesmentioning
confidence: 98%